2015
DOI: 10.1002/ejoc.201501179
|View full text |Cite
|
Sign up to set email alerts
|

Inverse γ‐Turn‐Inspired Peptide: Synthesis and Analysis of Segetalin A Indole Hemi­aminal

Abstract: Substitution of a peptide bond for an imine transforms the irreversible macrocyclization of peptides into a reversible process. The inherent cyclization tendency of a linear peptide is then analyzable through the equilibrium between the aldehyde and the imine by virtue of the higher reactivity of the corresponding linear peptide aldehyde. The tryptophan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Figure 3 C shows a zoomed in portion of the GC×GC chromatogram showing a series of alkyl phenols (cresols), with between one and four carbons present as side chains, shown in Figure 3 B. The cresols and indoles form from reactions of carbohydrates with one another ( Sad et al., 2008 ) or with amino acids ( Lamping et al., 2015 ; Meshram et al., 2013 ). Unlike the parent compounds, which are expected to be water soluble, these molecules possess log( K ow ) values >10, consistent with biocrude forming molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 C shows a zoomed in portion of the GC×GC chromatogram showing a series of alkyl phenols (cresols), with between one and four carbons present as side chains, shown in Figure 3 B. The cresols and indoles form from reactions of carbohydrates with one another ( Sad et al., 2008 ) or with amino acids ( Lamping et al., 2015 ; Meshram et al., 2013 ). Unlike the parent compounds, which are expected to be water soluble, these molecules possess log( K ow ) values >10, consistent with biocrude forming molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The tryptophan side chain of segetalin A aldehyde afforded a 12‐membered cyclic indole hemiaminal instead of the 18‐membered macrocyclic imine. [ 78 ]…”
Section: Bioactive Cyclopolypeptides From Seeds Of V Segetalismentioning
confidence: 99%
“…Segetaline A is a cyclohexapeptide (-Gly-Val-Pro-Val-Trp-Ala)-with estrogen-like activity that has been isolated from the seeds of Vaccaria segetalis. 38 Thionation with Lawesson's reagent (3) gave two products, A1 (Gly-thionated) and A2 (Gly-Ala-dithionated), which indicated that a clear selectively for the small (and less hindered) amino acids. The products A1 and A2 did not show any improved activity.…”
Section: Thionations Of Peptidesmentioning
confidence: 99%